The Effect of Puzzle Media on Arabic Learning Outcomes of Grade IV Students of Madrasah Ibtidaiyah 2 Limboto - Dali, Zulkifli; Damhuri, Damhuri; Nur Iman, Muhammad (Yayasan Daarul Qimmah Gorontalo, 2023)
This study aims to determine the effect of puzzle media on Arabic language learning outcomes in class IV of Madrasah Ibtidaiyah Negeri 2 Iimboto in 2022/2023 in which there is its application. Arabic learning outcomes are the results achieved by students in mastering knowledge of tarkib (sentence structure), mufradat (vocabulary), hiwar yaumiyyah (daily conversation), and tadrib (exercises). Which is the purpose of all of them including to understand the Qur'an and al-Hadith as a source of Islamic law. To determine the success of students in achieving Arabic learning outcomes, a measurement is needed that can affect learning outcomes. In this study, the measurement of learning outcomes using puzzle media. Puzzle media is an educational game tool that can stimulate children's abilities, played by unpacking pairs of puzzle pieces. Puzzle media is a game media consisting of pieces of pictures, boxes, letters, and numbers that form certain patterns so that students have the desire to complete the game quickly and precisely. The results of this study indicate that there is an effect of puzzle media on Arabic learning outcomes in class IV of Madrasah Ibtidaiyah Negeri 2 Iimboto in 2022/2023.